2003
DOI: 10.1046/j.1420-9101.2003.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Male fitness of honeybee colonies (Apis mellifera L.)

Abstract: Honeybees (Apis mellifera L.) have an extreme polyandrous mating system. Worker offspring of 19 naturally mated queens was genotyped with DNA microsatellites, to estimate male reproductive success of 16 drone producing colonies. This allowed for estimating the male mating success on both the colony level and the level of individual drones. The experiment was conducted in a closed population on an isolated island to exclude interferences of drones from unknown colonies. Although all colonies had produced simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…The variations rather may be due to different environmental conditions during nursing of young drones in different colonies. Kraus et al (2003) found clear evidence for variability in male mating success at the colony level for A. mellifera.…”
Section: Discussionmentioning
confidence: 85%
“…The variations rather may be due to different environmental conditions during nursing of young drones in different colonies. Kraus et al (2003) found clear evidence for variability in male mating success at the colony level for A. mellifera.…”
Section: Discussionmentioning
confidence: 85%
“…Individual drones from the more successful colonies had a higher siring success, which was represented in a higher proportion of offspring. Therefore Kraus et al (2003) conclude that the male reproductive success is a "major driver of natural selection in honeybees" and "selection through the male side appears to be an extremely important factor for colony fitness". These aspects might have supported the evolution of big males which, probably for physiological reasons, produce more sperm than small males and which develop a higher kinetic energy at flight which could be advantageous to outcompete other drones.…”
Section: Discussionmentioning
confidence: 98%
“…The sperm limitation hypotheses and the genetic variance hypotheses try to explain the causes for these multiple matings Tarpy and Page 2002;Kraus et al, 2004). Within a group of sister colonies the male mating success was, for unknown reasons, much higher in some colonies than the success of drones from other colonies in the group (Kraus et al, 2003). Individual drones from the more successful colonies had a higher siring success, which was represented in a higher proportion of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…where W j is the number of offspring sired by male j, n w the number of workers sampled and n m is the observed mating frequency of the particular queen (Kraus et al 2003). In order to test for a possible correlation between colony mating success and the siring success of individual males, we performed a Spearman rank correlation.…”
Section: Testing For a Colony-dependent Male Fitness Componentmentioning
confidence: 99%